Benefits of targeting each risk factor for cardiovascular death - Frutuoso, J. (2016)
Globally cardiovascular diseases are the main cause of death. In clinical practice we are able to advise an control several risk factors that might benefit our patients. But we know that trying to reach all goals we might chew more than we can swallow